Strategi Konservasi Kolaboratif Antar Kelembagaan Dalam Mendukung Pelestarian Kawasan Taman Nasional Gunung Merbabu di Kabupaten Boyolali - Bernadus Agus Hartanto; Jafron Wasiq Hidayat; Bambang Waluyo Hadi Eko Prasetiyono (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2019)
MerbabuMountain National Park (MMNP) as one of the conservation areas has an ecologically important role besides providing economic and social benefits to the surrounding community. The management of the MMNP area in order to be effective requires participation and the role of related parties. This study aims to formulate an integrated conservation strategy among related institutions to support the preservation of the MMNP area in Candisari Village, Gladagsari District, Boyolali Regency. This qualitative research uses the method of observation, interviews and literature studies which is then carried out processing data through SWOT analysis. The results of the research that show the role of related institutionsrequires synergistic collaboration. Collaborative strategy of inter-institutional roles that can support the preservation of MMNP area, that are1) Collaboration between stakeholders in managing the potential of both water resources and tourism, 2)Inventory of biodiversity potential inside and outside the region and the preparation of natural tourism site design in the utilization zone involving the community, 3) Synergizing regional development policies and programs in the MMNP buffer zone with the management of the MMNP area, 4)Develop a multi-stakeholder program for community empowerment around the MMNP area, 5) Encourage multi-stakeholder cooperation through multisectoral forums to support the management of the MMNP, 6) Management of tourism potential within and outside community-based areas in a synergistic manner, 7) Increased environmental awareness across the Gunung Merbabu region across sectors, 8) Collaborative mitigation of disasters or disasters in the MMNP region.